A `pornographer' of science. - Patel, Kam (Times Higher Education Supplement, 1995)
Reports on the practice of science on a television program in Great Britain by geneticist Steve Jones. Lack of research grants as a major factor for Jones' decision; Answers to criticisms that science on television corrupts the profession; Views on government support on genetic research; Explanation of analyzing genetic genes.